Ordos Mausoleum of Genghis Khan: History and Modernity - Nomin D. Tsyrenova; Chingis Ts. Tsyrenov (Монголоведение)
Introduction. The memory of the great Mongol conqueror and his empire still remains the focus of attention of scientists, writers and statesmen and influences modern cultural and political processes. The purpose of this article is that the article provides brief information about the history of creation and the current state of the Ordos mausoleum in honor of Genghis Khan. It is believed that this memorial contains personal belongings and symbols of the power of the great Mongol conqueror. Materials and methods. When conducting the study, a complex of heterogeneous sources was used, represented by Internet publications, journal articles and statistical data related to the Ordos Mausoleum of Genghis Khan. Analytical tools, determined by a systematic approach to the object of study, include the method of retrospective analysis, comparative historical and historical typological methods and systems analysis. The combination of retrospective and problem-chronological methods with the principles of historicism and objectivity made it possible to consider events objectively and in the context of their relationships. Results. Based on current translated data from Chinese publications, an analytical description of the studied object and its tourism potential is presented. It was revealed that the creation of a tourist complex at the Mausoleum of Genghis Khan was initiated by the private development corporation Donglian in 2001. Conclusion. The Ordos Mausoleum of Genghis Khan and the tourist complex of the same name can be considered as one of the modern forms of the cult of veneration of Genghis Khan, as well as a striking example of the pragmatic implementation of the policy of memory on the part of the official Chinese authorities in relation to the great conqueror and the Mongol Empire as a whole. Thanks to a creative approach to the practical implementation of the course of reforms and openness in the field of culture of small peoples, the central and regional Chinese authorities were able to create a completely harmonious synthesis of Chinese and Mongolian cultural traditions, commercialize and synthesize the cultural and aesthetic-symbolic potential of the memory of the Mongol Empire and modern Chinese statehood represented by Genghis Khan and the memorial complex in his honor in Ordos, relying on regional public-private partnerships. Last but not the least, constructive cooperation between the regional historical community, private business and the party-state administration of the Ordos urban district has borne fruit.